2020
DOI: 10.3389/fbioe.2020.00890
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Injectable Nanofibrous Extracellular Matrix Hydrogel With an Integrin αvβ3 Ligand to Improve Endothelial Cell Survival, Engraftment and Vascularization

Abstract: Endothelial cell (EC) transplantation via injectable collagen hydrogel has received much attention as a potential treatment for various vascular diseases. However, the therapeutic effect of transplanted ECs is limited by their poor viability, which partially occurs as a result of cellular apoptosis triggered by the insufficient cell-extracellular matrix (ECM) engagement. Integrin binding to the ECM is crucial for cell anchorage to the surrounding matrix, cell spreading and migration, and further activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…In this study, we built upon the DS–SILY therapeutic by further functionalizing with an angiogenic peptide to stimulate angiogenesis through integrin-mediated VEGF pathway activation. The cyclic octapeptide LXW7 has been shown to specifically target the αvβ3 integrin on ECs when tethered to a surface and can induce targeted and controlled angiogenesis through VEGFR2 phosphorylation . We hypothesized that by combining the collagen-binding decorin mimetic with the proangiogenic peptide (LXW7–DS–SILY), we could capitalize on the ability of DS–SILY to suppress collagen matrix degradation and promote angiogenesis indirectly through integrin-mediated VEGFR2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we built upon the DS–SILY therapeutic by further functionalizing with an angiogenic peptide to stimulate angiogenesis through integrin-mediated VEGF pathway activation. The cyclic octapeptide LXW7 has been shown to specifically target the αvβ3 integrin on ECs when tethered to a surface and can induce targeted and controlled angiogenesis through VEGFR2 phosphorylation . We hypothesized that by combining the collagen-binding decorin mimetic with the proangiogenic peptide (LXW7–DS–SILY), we could capitalize on the ability of DS–SILY to suppress collagen matrix degradation and promote angiogenesis indirectly through integrin-mediated VEGFR2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…These implants formed a block-like structure after 4 weeks, similar to an expanded vascular plexus. This model is one of the most promising models for research in the fields of angiogenesis, 3D cell culture, vascular growth factors, and cell-to-cell communication [ 103 , 104 ]. It resembles the progression of IH observed in infants and young children, from the proliferative to the regressive stage.…”
Section: Three-dimensional (3d) Model Of Cell Culture In Vitromentioning
confidence: 99%
“…Collagen has been served as a biodegradable scaffold material and extensively employed in research on vascular regeneration studies, supporting and promoting angiogenesis . Prior research has shown that collagen regulates the migration and adhesion of endothelial cells by furnishing cell adhesion sites and facilitating cell-to-cell interactions. , Through binding to cell receptors, collagen initiates a cascade of cellular signaling pathways that impact various functions, including the survival, proliferation, and migration of vascular endothelial cells. , Additionally, collagen can modulate inflammatory responses, contributing to wound healing and the reconstruction of endothelial function . ADSCs are a type of multipotent stem cell found in adipose tissue, possessing the potential for multilineage differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Through binding to cell receptors, collagen initiates a cascade of cellular signaling pathways that impact various functions, including the survival, proliferation, and migration of vascular endothelial cells. 32,33 Additionally, collagen can modulate inflammatory responses, contributing to wound healing and the reconstruction of endothelial function. 34 ADSCs are a type of multipotent stem cell found in adipose tissue, possessing the potential for multilineage differentiation.…”
Section: Introductionmentioning
confidence: 99%